Perceived Relationship between Remuneration, Recognition and Job Satisfaction among Public School Teachers in Nairobi County Kenya - Oyaro, Samwel Makori (IJRDO- Journal of Educational Research, 2018)
The study sought to determine the perceived relationship between remuneration, recognition and job satisfaction among public secondary school teachers in Nairobi County. Therefore, 240 teachers from twelve randomly selected public schools completed the job satisfaction questionnaire. Data was analyzed using descriptive statistics and Pearson product moment. The results showed there is a positive relationship between remuneration, recognition and job satisfaction.